1045 COMPARISON OF CEPHALIC VEIN VERSUS SUBCLAVIAN APPROACH FOR LEFT BUNDLE BRANCH PACING: A SINGLE CENTRE EXPERIENCE. (15th December 2022) - Fabbricatore, Davide; Valeriano, Chiara; Gallinoro, Emanuele; Paolisso, Pasquale; De Schouwer, Koen; De Potter, Tom
Abstract: Background: left bundle branch area pacing (LBBAP) is a recently introduced pacing method and has been described suggesting the subclavian venous puncture as the preferred approach. Aim: This is the first study comparing the cephalic access to the "classical" subclavian approach for the implantation of LBBAP. Methods: Retrospective study evaluating all consecutive patients undergoing LBBAP at the cardiovascular research Centre of Aalst in Belgium from October 2020 to February 2022. LBBAP was performed either using cephalic or subclavian approach at the operator's discretion and for one of lead or both in case of multiple leads. In both cases, dedicated delivery sheaths were used for the implantation of the ventricular lead in the left bundle branch area. Implant success, complications, procedural and pacing characteristics were analyzed at implant. Results: 81 patients were enrolled (age 78.20±11.47), 44 (54%) of which in the cephalic groups. LBBAP was successful at first attempt in 97% of the population, without significant differences between groups (P=0.886); dislocation of leads after the slitting occurred in 5 (11, 4%) and 3 (8, 1%) patients (P=0, 625). Procedural and X-ray times were not significantly different in the two groups. Pacing parameters were normal at the end of the procedure in both groups. Conclusion: This is the first study comparing safety and feasibility of LBBAP of a cephalic versus the subclavian one. Procedural success and times were not affected from the choice of cephalic instead than subclavian access. Periprocedural dislocation rates did not differ between groups. Complete cephalic group* (N=44) Subclavian ± cephalic group* (N=37) Total (N=81) p value sex 0.277 - M 29 (65.9%) 20 (54.1%) 49 (60.5%) - Mean AGE (SD) 77.64 (11.38) 78.86 (11.71) 78.20 (11.47) 0.326 - Mean BMI (SD) 28.25 (5.36) 26.57 (4.90) 27.47 (5.18) 0.230 - Median (Q1, Q3) 81.00 (74.00, 85.00) 82.00 (74.00, 87.00) 82.00 (74.00, 86.00) - Mean procedural time (SD) 92.85 (27.46) 97.53 (27.92) 94.93 (27.57) 0.734 - Mean XRAY time (SD) 13.36 (10.30) 15.33 (9.43) 14.33 (9.83) 0.357 - Success rate, Mean (SD) 0.98 (0.15) 0.97 (0.17) 0.97 (0.16) 0.886 Impedance at implant 485.64 (120.30) 464.89 (107.04) 475.45 (113.42) 0.418 Threshold at implant 0.70 (0.34) @ 0, 4 msec 0.71 (0.29) @ 0.4 msec 0.71 (0.31) 0.627 Sensing at implant 9.87 (4.40) 7.85 (4.27) 8.90 (4.41) 0.084 Periprocedural dislocation 5 (11.4%) 3 (8.1%) 8 (9.9%) 0.625 *In the group "complete cephalic" all leads (in case of more than one) were implanted through the cephalic vein; in the group "subclavian ± cephalic" the LBBAP lead was implanted through the subclavian vein and the other leads (if needed) could have been placed indistinctly in cephalic or subclavian vein. ° Described as the time from the arrival of the patient to the exit from the operating room.